Sport-related concussion in children: a comprehensive review of current evidence - Michałowski, Maciej; Sudomir, Maria; Wilkowska, Krystyna; Kaczorowski, Wojciech; Knysak, Karol; Maj, Alicja; Szczerba, Mateusz; Hejnosz, Aleksandra; Jastrzębski, Michał; Piątek, Maja (Quality in Sport, 2025)
Background: Sport-related concussion (SRC) is a mild traumatic brain injury caused by direct or indirect forces to the head and represents a significant proportion of paediatric sports injuries. Aim: To provide clinicians with concise, evidence-based guidance for accurate assessment and management of SRC in paediatric population and highlight areas requiring further research. Methods: A narrative review of PubMed and Google Scholar included original studies, reviews, meta-analyses, and guidelines addressing epidemiology, risk factors, diagnosis, and management. Results: SRC in children presents with heterogeneous symptoms, often without loss of consciousness. Common features include headache, dizziness, confusion, amnesia, visual disturbances, affective liability, and learning difficulties. Assessment can be supported by tools such as CRT6 for early recognition and SCAT6, Child SCAT6, SCOAT6, and Child SCOAT6 for structured cognitive and neurological evaluation. Protective equipment, including helmets and mouthguards, may reduce concussion risk in some sports, though evidence is mixed. Management emphasizes timely assessment, avoidance of prolonged rest, and a gradual return-to-school and activity plan, with most children returning to school within 10 days. Conclusions: SRC remains a major concern in paediatric population. Early recognition, structured assessment, and comprehensive prevention strategies are essential to improving outcomes.